Perbandingan Ukuran Lubang Tanam 60 x 60 x 40 cm dengan 80 x 80 x 60 cm terhadap Pertumbuhan Vegetatif Tanaman Kelapa Sawit Belum Menghasilkan Umur Satu Tahun - Toto Suryanto (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
This study aims to determine the best planting hole size for vegetative growth of oil palm plants has not produced one year of age and to obtain planting hole size that can be recommended for planting oil palm has not produced one year of age. This research was conducted at Experiment Garden Citra Widya Edukasi Polytechnic of Palm Oil, Bekasi on January 6th, 2015 to February 6th, 2016. Analysis of N, P, and K leaf content was carried out in Agronomy and Horticulture Laboratory, Faculty of Agriculture, IPB. This study uses Completely Randomized Design of one factor. The tested treatments were two planting hole sizes of 60 x 60 x 40 cm (A0) and 80 x 80 x 60 cm (A1). Each treatment was repeated twice so that there were 4 units of experimental unit. Data analysis used is ANOVA Test and Advanced Test of DMRT (Duncan Multiple Range Test) at 5% level. The results showed that plant size ratio significantly affected the plant height, stem diameter, wet weight, and dry weight of crown, but no significant effect on leaf number, leaf area, and stomatal density. The best treatment was seen in the planting hole size 80 x 80 x 60 cm for all parameters showing the real difference. Size of the best planting hole is 80 x 80 x 60 cm showed high levels of N leaf nutrient, nutrient content of P leaf is considered optimal, and K leaf nutrient content is classified as less.